Simultaneous determination of hypericin and hyperforin in human plasma with liquid chromatography-tandem mass spectrometry - Riedel, Klaus-Dieter; Rieger, Karin; Martin-Facklam, Meret; Mikus, Gerd; Haefeli, Walter E.; Burhenne, Jürgen (Journal of chromatography, 2004)
A selective and sensitive method for the simultaneous determination of hypericin and hyperforin—the two main active ingredients of St. John's Wort (SJ…
Gesehen am 19.05.2021